Literature Review of Competitive Advantage of Creative Economy in Guangdong-Hong Kong Macau Greater Bay Area - Liyan Cao; Shamsudin, Mohd Farid (Asia Pacific Journal of Social Science Research, 2024)
This literature review explores the competitive advantage of the creative economy in the Guangdong-Hong Kong-Macau Greater Bay Area (GBA). Grounded in the theoretical frameworks of competitive advantage, it examines key concepts such as the creative industry and the broader creative economy. The review highlights the unique attributes and strengths of the GBA, identifying how its strategic positioning and resources contribute to its competitive edge. Despite the region’s strengths, the review identifies significant research gaps, particularly in understanding the integration and collaboration among the GBA cities and the impact of global economic trends on the local creative economy. Future research can provide deeper insights into enhancing the GBA’s competitive position in the global creative landscape by addressing these gaps.